Impact of Different Rainfall Intensity and Duration on Flash-Flood Events on a Steep-Sloped Ungauged Watershed - Gergely Ámon; Katalin Bene (Chemical Engineering Transactions, 2023)
Changing climate conditions increase rainfall intensity and cause a growing number of flash flood events. Due to flash floods, problems with water damage prevention (urban area floods, erosion of natural watersheds) are increasing; these events also make the sustainable maintenance of watersheds more challenging. Hungarian watersheds are ungauged; very little historical or real-time data is available, making it difficult to understand the hydrological processes occurring during flash flood events. When only limited data is available, numerical models help predict peak flows and runoff volume. Additionally, a comparison of different models and parametrizations could be a helpful tool to reduce prediction uncertainty. This paper evaluates the impact of different rainfall intensities and durations on flash flood events at the ungauged watershed of the Morgó-creek on the northern side of Hungary. Land use conditions are primarily natural, with urban areas close to the outlet point. Hydrological and hydrodynamical models were used to apply different scenarios to determine the sensitivity of the whole watershed system based on typical precipitation events in time and intensity. The models predicted different peak flows and timing for flash floods. Using both models for comparison is recommended for flash flood prediction to compensate for the lack of measured data.